Le monde des lecteurs de Spore(1.2) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Dans notre rubrique ' À lire ' :le toujours pertinent, informatif et fascinant Spore.- ECHO